(untitled) (Bangladesh Journal of Animal Science, 2012)
The study was undertaken to investigate the effects of concentrate supplementation with different protein levels on intake, digestibility and growth performance of Red Chittagong (RC) heifers fed urea molasses straw (UMS) based diet. Twelve RC heifers having average live weight of 124.83±43.15 kg and aged between 8 to 14 months were selected for 90 days feeding trial. Animals were divided into four groups having three animals in each and were randomly assigned to four dietary treatments in a Randomized Block Design (RBD). The experimental diets were formulated using urea molasses straw (UMS), German grass (Echinochloa grousgalli) with or without concentrate mix (having different levels of protein). All the animals received UMS ad libitum and German grass at the rate of 20% of total DM intake. In addition to UMS and German grass of control diet T0, animals on diets T1, T2 and T3 were supplied with concentrate mixture at the rate of 10% of DM intake containing 15, 20 and 25% CP, respectively. Average daily DM intake was 2.65, 3.06, 2.62 and 2.86 kg/100 kg LW for diets T0, T1, T2 and T3, respectively and the difference was non significant (P>0.05). The digestibility of DM, CP, EE, NFE and digestible nutrients (DCP, DEE and DNFE) for diets T1, T2 and T3 was significantly higher than those for diet T0. The daily average liveweight gain of RC heifers fed diets T0, T1, T2 and T3 were 100, 275, 333 and 291 g respectively (P<0.01). Concentrate mixture having 20% crude protein may be supplemented at the rate of 10% of DM intake per day for optimum growth of Red Chittagong heifers. DOI: http://dx.doi.org/10.3329/bjas.v37i1.9861 BJAS 2008; 37(1): 10-16